Bud and root development of turmeric (Curcuma longa L.) rhizome - RAVINDRAN, K K SHERLIJA, K UNNIKRISHNAN, P N (Journal of Spices and Aromatic Crops, 1999)
The structure and organization of axillary bud and adventious root in turmeric (Curcuma longa) rhizome was studied. The mother rhizome is bulbous with smaller internodes compared to branches (fingers) which have long internodes. The axillary buds develop from the axile of scale leaf of the rhizome. The secondary branches of the rhizome develop from the primary branches. Roots originate from the intermediate zone of the rhizome. The root apicalmeristem is of the open type the three sets of structural initials and possess a distinct quiescent centre.